2014
DOI: 10.1007/s11095-014-1310-x
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Orthopedic Implant Failure Using Macromolecular Imaging Agents

Abstract: Purpose To develop and evaluate diagnostic tools for early detection of wear particle-induced orthopaedic implant loosening. Methods N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer was tagged with an near infrared dye and used to detect the inflammation induced by polymethylmethacrylate (PMMA) particles in a murine peri-implant osteolysis model. It was established by inserting implant into distal femur and with routine PMMA particles challenging. The osteolysis was evaluated by micro-CT and histological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Recently, a polymeric nanocarrier system targeting inflammatory cells was revealed by a series of experiments performed by a group of researchers at the University of Nebraska, to be enriched at inflamed sites with a few animal models. 8 , 77–80 The system makes use of water-soluble copolymers of N -(2-hydrocpropyl)methacrylamide (HPMA), that were originally designed for cancer chemotherapy due to the meritorious properties of the nanoparticles. These include an enhanced permeability and retention effect, water-solubility, low immunogenicity, and high stability.…”
Section: Detection and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a polymeric nanocarrier system targeting inflammatory cells was revealed by a series of experiments performed by a group of researchers at the University of Nebraska, to be enriched at inflamed sites with a few animal models. 8 , 77–80 The system makes use of water-soluble copolymers of N -(2-hydrocpropyl)methacrylamide (HPMA), that were originally designed for cancer chemotherapy due to the meritorious properties of the nanoparticles. These include an enhanced permeability and retention effect, water-solubility, low immunogenicity, and high stability.…”
Section: Detection and Diagnosismentioning
confidence: 99%
“…These include an enhanced permeability and retention effect, water-solubility, low immunogenicity, and high stability. 81 , 82 While HPMA copolymers have been labeled with near-infrared dye 800CW and radioisotope 125 I for imaging purposes 78 , 80 and loaded with a drug dexamethasone for therapeutic intention, 77 , 78 it is anticipated that conjugates of these copolymers with other radioisotopes such as 111 In, 99m Tc, 18 F, and 64 Cu, and other drugs, will be explored in the future in order to achieve the clinical use of nanocarriers for early diagnosis and effective treatment of periprosthetic osteolysis. These nanocarriers are in contrast to FDG-labeled probes, which are not feasible for drug conjugation as they are too nonspecific and lack durability.…”
Section: Detection and Diagnosismentioning
confidence: 99%
“…There was only one paper that measured behavior, as a surrogate for pain assessment . Six papers examined biomarkers with four focusing on blood, urine or synovial fluid and two using imaging biomarkers …”
Section: Resultsmentioning
confidence: 99%
“…LPS contamination of particles, either by incubating the particles in LPS‐containing solution or by administering LPS via intraperitoneal injection, was shown to exacerbate peri‐implant osteolysis . Early diagnosis was assessed in two studies; one used a macromolecular bioimaging approach and one used a bone turnover biomarker . Both studies showed that early detection of osteolysis is feasible in highly controlled preclinical animal models.…”
Section: Resultsmentioning
confidence: 99%
“…In this analysis, we also found the 125 I activity (representing the amount of P-Dex) between the particle-injected left femur and non-particle-injected right femur was not significantly different, which was not consistent with our previous findings. 17, 28 The systemic exposure of the conjugate increased when the MW was raised. The AUC 0-∞ (blood) of the conjugates positively correlated with the MW of the conjugates and Cl of the polymers was negatively correlated to the MW of the polymers.…”
Section: Discussionmentioning
confidence: 99%